First report of phytoplasma groups 16SrI and 16SrV infecting Brassica napus in China. (December 2019) - Tang, Qian; Fu, Yanping; Ma, Ming; Yao, Yao; Qu, Zheng; Xie, Jiatao; Cheng, Jiasen; Jiang, Daohong
Abstract: Rapeseed ( Brassica napus L.) is an important cruciferous crop worldwide. In this study, we collected five rapeseed samples with typical symptoms induced by phytoplasmas from Wuhan and Ezhou, Hubei Province, China, and E'erguna, Neimenggu Province, China. We successfully identified phytoplasmas from these samples via nested PCR amplification using phytoplasma-specific primer pairs. We also carried out phylogenetic analyses and grouped these phytoplasmas with the online tool i PhyClassifier. As a result, the phytoplasmas in samples EZ and NMG with witches'-broom and sample WH3 with dwarfing belonged to subgroup 16SrI–B, while the phytoplasmas in sample WH1 with fasciation and sample WH2 with peduncle clustering were members of subgroup 16SrV–H. This is the first report of phytoplasmas infecting rapeseed in China and of group 16SrV infecting rapeseed. We further investigated the host range of groups 16SrI and 16SrV and found group 16SrI in 307 plant species belonging to 230 genera of 83 families, while group 16SrV was identified in 65 species belonging to 47 genera of 30 families. The possible host expansion and host jumping of group 16SrV and the potential risk of phytoplasmas to rapeseed were also discussed. Highlights: Phytoplasmas infect rapeseed in China. Phytoplasmas in group 16SrV infect rapeseed. Phytoplasmas in groups 16SrI and 16SrV have a broad host range.